2009
DOI: 10.1007/s10143-009-0190-8
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes following surgical resection of myxopapillary ependymomas

Abstract: Myxopapillary ependymomas, a specific tumor variant of spinal cord ependymomas, occur most commonly in the lumbosacral region. During the study period, 1,013 patients underwent surgery for spinal cord tumors. Fifty-two of the patients had a myxopapillary ependymoma. Forty-eight of these patients underwent surgery at our institutions. There were four patients who came for consultations only. Fourteen pediatric patients were diagnosed with myxopapillary ependymoma. The overall average age at which a patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
2
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 55 publications
4
87
2
9
Order By: Relevance
“…Bagley and colleagues 7 and Chao and colleagues 11 demonstrated no benefit in recurrence-free survival for patients treated with adjuvant radiotherapy after surgery. Akyurek and colleagues, 2 on the other hand, found that adjuvant radiotherapy was associated with better outcomes for both patients who underwent GTR and those who underwent STR.…”
Section: ©Aans 2013mentioning
confidence: 99%
See 2 more Smart Citations
“…Bagley and colleagues 7 and Chao and colleagues 11 demonstrated no benefit in recurrence-free survival for patients treated with adjuvant radiotherapy after surgery. Akyurek and colleagues, 2 on the other hand, found that adjuvant radiotherapy was associated with better outcomes for both patients who underwent GTR and those who underwent STR.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…Myxopapillary ependymomas appear to be particularly aggressive in these younger individuals. 7,27 Consensus on optimal surgical and/or adjuvant treatment will depend on which of these modalities provides maximal tumor control. It is unlikely that a randomized controlled clinical trial will be designed to conclusively answer this question.…”
Section: ©Aans 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…pinal cord ependymomas are slow growing, not very infiltrative, and well-demarcated tumors of neuroectodermal origin arising from ependymal cells in the central canal of the spinal cord and filum terminale, 1,8,21,26,31,40 or even from heterotopic ependymal cells in the spinal canal. 5,37 These ependymomas occur more frequently in middle age (40-60 years of age) and represent 60% of cases of intramedullary spinal cord tumors.…”
mentioning
confidence: 99%
“…Although there is evidence that Grade I ependymomas are more aggressive in children compared with adults, 5,38,45 our institutional experience suggests that GTR can be achieved safely, in Table 1). Sagittal pre-(A) and postoperative (B) T1-weighted MR images after contrast administration from a patient with a spinal Grade II (classic) ependymoma.…”
Section: Discussionmentioning
confidence: 83%